Rules of origin: an economic analysis and proposals for multilateral action (SELA CaracasVE, 1993)
Defines rules of origin. Describes and analyzes alternative methods for determining origin. Analyzes the economics of rules of origin, and in particular the role these rules play in determining levels of protection in different markets within preferential trading areas. Also discusses rules of origin in the context of GATT.
DC